Peer Victimization and Empathy for Victims of Bullying: A Test of Bidirectional Associations in Childhood and Adolescence - Trach Jessica; Garandeau Claire; Malamut Sarah (Wiley, 2025)
Anti-bullying interventions often assume that knowing how it feels to be bullied increases empathy for victims. However, longitudinal research on actual experiences of bullying and empathy is lacking. This study investigated whether within-person changes in victimization predicted changes in empathy over one year using random-intercept cross-lagged panel models (RI-CLPMs). Self- and peer-reported victimization, and cognitive and affective empathy for victims were measured in a sample of 15,713 Finnish youth (Mage = 13.23, SDage= 2.01, 51.6% female; 92.5% had Finnish-speaking parents; data was collected in 2007-2009 when information about participants’ race/ethnicity was not available due to ethical guidelines for the protection of personal information). Results indicated small, positive longitudinal associations from victimization to cognitive empathy. Implications for empathy-raising interventions are discussed.